BABA PERFUME MARKETING STRATEGY USING DIGITAL MARKETING IN MEDAN DENAI COMMUNITY - Lubis, Muya Syaroh Iwanda; Nst, Asrindah; Hasugian, Buyung Solihin (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
This study aims to determine the marketing strategy for people's interest in buying in the Medan Denai area for this Baba Parfum product. The data collection technique chosen to process the data is qualitative, which is given a form and made to be selected as a sample of 25 respondents. The data collection method is in the form of a questionnaire. Baba Parfum, a local perfume brand that adopts a management system that involves a team network in their product sales efforts. This network system has proven effective in increasing sales of Baba Parfum products. Marketing strategy by mastering social media to see the products marketed as many as 93.5% of consumers are satisfied with the digital marketing of Baba Parfum and its marketing strategy. Consumers also use payment technology such as e-money through Gopay Ovo, and funds can be seen that consumers know the product in the era of digital marketing and sales that are developing well. Therefore, the development of Baba Parfum products in the current era has a great influence on the company's profitability so that the selling price is quite good and is able to attract consumers.